REVIEW ON THE KRAS PROTEIN MUTATIONS IN COLORECTAL CANCER: MOLECULAR PATHWAYS AND THERAPEUTIC OPPORTUNITIES - Salem, Wisal; Abdul Majeed, Rana; Al-Tamimi, Shatha (Antis-Publisher, 2026)
Objective: The mutations in the KRAS proteins are the most crucial molecular events that contribute to the initiation and development of colorectal cancer (CRC). Method:Recent progress with high-resolution genomics further illuminated the various biological implications of specific KRAS alleles to show that individual sub-types of mutations possess specific oncogenic capabilities, and therapeutic weaknesses. Results:KRAS mutations (especially G12D, G12V, and G13D) lead to constitutive activation of downstream signaling pathways that mediate cell survival, cell proliferation, and cell differentiation, promoting tumor progression, metabolic reorganization, EMT, resistance to anti-EGFR monoclonal antibodies, immunosuppressive microenvironment formation, and altered signaling networks including PI3K/AKT and RAF/MEK/ERK. Novelty: The knowledge of the specific molecular implications of KRAS mutations provides a growing world of opportunities to treat patients with CRM personally and provide better outcomes, including allele-specific inhibitors, dual therapy strategies, synthetic lethality, immunotherapy repression, and metabolic therapy.